2006
DOI: 10.1111/j.1365-2435.2006.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter flammability in some semi‐arid Australian woodlands

Abstract: Summary 1.Wildfires strongly influence the biotic composition and carbon cycle of many ecosystems. Plant species provide the fuel for wildfires, but vary widely in their flammability. This study aimed to determine what plant characteristics control leaf litter flammability and to clarify how they are related to other functional traits. 2. Litter flammability varied across 14 tree species occurring in a mosaic of five floristic associations. 3. Differences in heat-release rate between species were driven by lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
229
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(251 citation statements)
references
References 25 publications
16
229
1
5
Order By: Relevance
“…Scarff and Westoby (2006) reported that large leaves created an open litter bed structure which burned more rapidly because it was better ventilated. Leaf size was shown to be the most important trait influencing both the intensity and sustainability of litter fires, more than chemical factors known to influence flammability, such as oils and lignin content (Vines 1981;Parker and LeVan 1989).…”
Section: Assessment Of the Flammability Of Heterogeneous Dead Fuelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Scarff and Westoby (2006) reported that large leaves created an open litter bed structure which burned more rapidly because it was better ventilated. Leaf size was shown to be the most important trait influencing both the intensity and sustainability of litter fires, more than chemical factors known to influence flammability, such as oils and lignin content (Vines 1981;Parker and LeVan 1989).…”
Section: Assessment Of the Flammability Of Heterogeneous Dead Fuelsmentioning
confidence: 99%
“…The litters of each species presented their own flammability mainly depending on their composition and bulk density because this variable, which determines fuel compaction in space, controls the rate of oxygen that can flow through the fuels as well as the heat transfer between fuel particles (Scarff and Westoby 2006). The moisture content of the oven-dried litter samples was assumed to not affect the flammability as it was very low.…”
Section: Assessment Of the Flammability Of Heterogeneous Dead Fuelsmentioning
confidence: 99%
See 3 more Smart Citations